2018
DOI: 10.1016/j.colsurfb.2018.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose hydrogel loaded with lipid nanoparticles for localized cancer treatment

Abstract: The use of hybrid materials, where a matrix sustains nanoparticles controlling the release of the chemotherapeutic drug, could be beneficial for the treatment of primary tumors prior or after surgery. This localized chemotherapy would guarantee high drug concentrations at the tumor site while precluding systemic drug exposure minimizing undesirable side effects. We combined bacterial cellulose hydrogel (BC) and nanostructured lipid carriers (NLCs) including doxorubicin (Dox) as a drug model. NLCs loaded with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 72 publications
(93 reference statements)
0
35
0
2
Order By: Relevance
“…In this research work, cationic and neutral doxorubicin loaded systems were evaluated in vitro against MDA‐MB‐231 cells followed by an in vivo assay using an orthotopic breast cancer mouse model. Outcomes achieved showed low encapsulation efficiency (48%) and fast release for the cationic drug loaded system while higher encapsulation (97%) and sustained drug release was obtained for the neutral drug loaded system . Ngwabebhoh et al .…”
Section: Nc In Biomedicinementioning
confidence: 98%
“…In this research work, cationic and neutral doxorubicin loaded systems were evaluated in vitro against MDA‐MB‐231 cells followed by an in vivo assay using an orthotopic breast cancer mouse model. Outcomes achieved showed low encapsulation efficiency (48%) and fast release for the cationic drug loaded system while higher encapsulation (97%) and sustained drug release was obtained for the neutral drug loaded system . Ngwabebhoh et al .…”
Section: Nc In Biomedicinementioning
confidence: 98%
“…27 It may be advantageous to use hybrid biomaterials in which a matrix retains nanoparticles that control the release of the chemotherapeutic drug for the treatment of primary tumour before or after surgical operation. BC hydrogel and nanostructured lipid carriers (NLCs) were assembled by Cacicedo et al (2018). 208 The cationic doxorubicin (Dox) and neutral Dox which used as a drug modal were loaded into NLCs, resulting in the NLC-NH mixture.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…BC hydrogel and nanostructured lipid carriers (NLCs) were assembled by Cacicedo et al (2018). 208 The cationic doxorubicin (Dox) and neutral Dox which used as a drug modal were loaded into NLCs, resulting in the NLC-NH mixture. This study indicated that BC-NLC-NH has a considerable effect on the reduction in tumour growth, prevalence of metastasis, and local drug toxicity.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…The literature describes several in vivo studies in which BC was applied, from the replacement of abdominal skin [23], dorsal implants [24], and brain and breast cancer treatments in rats [25,26], to vascular stents [15,27,28]. Other studies revealing the use of BC as artificial skin, artificial blood vessels and microvessels, wound dressing of secondor third-degree burn ulcers, and dental implants [23] were also reported.…”
Section: Bacterial Cellulosementioning
confidence: 99%